THE EFFECT OF TOTAL PHSYICAL RESPONSE (TPR) METHOD ON STUDENTSâ€™ SPEAKING ACHIEVEMENT; A CASE OF NINETH GRADE STUDENTS OF SMPN 1 KABAWO - Sitti, Wa Ode; Nurnia, Nurnia; Siam, Siam (Journal of Teaching of English, 2019)
This study was aimed at finding out whether there is a significant effect of Total Physical Response (TPR) method on studentsâ€™ speaking achievement. The research question addressed was â€œis there Â anyÂ  significant Â effect Â of Â Total Â Physical Â Response Â (TPR) method on studentsâ€™ speaking achievement?â€ The design of study was quasi experimental design by using two classes, namely experimental class and control class. This study involved the ninth grade students of SMPN 1 Kabawo who were registered in the academic year 2017/2018. The instrument of the study was oral test where the students performed in front of the class orally about how to make a glass of ice lemon in 3 minutes. The study used independent sample t- test to analyze the data. The result showed that the studentsâ€™ speaking score in experimental class (3.12) was higher than studentsâ€™ speaking score in control class (2.23). The result of hypothesis testing revealed that the level of significant was 0.00. It means that there was a significant difference on studentsâ€™ speaking achievement after being taught by using total physical response.Â Keywords: Speaking, Teaching Speaking, Total Physical Response